2004
DOI: 10.1038/modpathol.3800141
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of normal and reactive spleen

Abstract: Spleen is surgically removed for both non-neoplastic and neoplastic pathologies. A significant proportion of splenectomy specimens require distinguishing between reactive and neoplastic conditions (eg lymphoma). To establish a 'normal' reference range for the spleen lymphocyte subsets, fresh samples of benign, reactive spleens obtained from adult patients (N ¼ 12) and samples of normal spleen obtained from cadaveric transplant donors (N ¼ 14) were analyzed using three-and four-color flow cytometry. Study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…The events were plotted on dot plot and different populations were gated based on their light scatter profiles. 31 Our results showed that PEITC treatment modestly reduced granulocyte and monocyte populations (Fig 2B & C). Surprisingly, PEITC treatment had no effect on the lymphocyte population ( Fig 2D).…”
Section: The Effect Of Peitc On Circulating Leukocytesmentioning
confidence: 58%
See 1 more Smart Citation
“…The events were plotted on dot plot and different populations were gated based on their light scatter profiles. 31 Our results showed that PEITC treatment modestly reduced granulocyte and monocyte populations (Fig 2B & C). Surprisingly, PEITC treatment had no effect on the lymphocyte population ( Fig 2D).…”
Section: The Effect Of Peitc On Circulating Leukocytesmentioning
confidence: 58%
“…To identify monocytic and lymphocytic cell subsets, cells were gated based on their light scatter profiles on dot plots. 31 The monocytic cell population was used to evaluate effects on MDSCs and the lymphocytic population was used to determine T-cell modulations. Accuri C6 flow cytometer software was used to compare CD11b, CD33, CD34 or CD4 expressing cell populations as well as surface densities for these receptors in control and PEITC treated groups.…”
Section: Methodsmentioning
confidence: 99%
“…Saturating amounts of allophycocyanin cy7 (APCCy7)-CD3, fluorescein isothiocyanate (FITC)-CD4 and phycoerythrin (PE)-CD8 conjugated antibodies were added to the cells and incubated for 45 min. After incubation washout the unbound fluorochome and suspend the cells in the sheath fluid for FACS analysis [9].…”
Section: Immunophenotypingmentioning
confidence: 99%
“…Both groups were subdivided into five subgroups (six mice each) according to the duration of sacrifice; zero, The spleens of mice of all subgroups were aseptically collected at the same duration of sacrifice. They were preserved at -20 o C to be processed for the detection of IgE antibodies in their lymphocytes by flow cytometry [16,20].…”
Section: Animalsmentioning
confidence: 99%
“…The cell pellets of each subgroup of mice (6 mice) were collected and pooled together and were resuspended in a dose of 5 x 10 5 cells / tube in three ml PBS and subjected to immunofluorescent staining. Fluorochrome intensity was measured by monoparameter flow cytometry [16,[20][21][22][23][24].…”
Section: Preparation Of Splenic Suspensionsmentioning
confidence: 99%